Blood insulin level biosensor for athltes - Deng, X. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: The pancreas releases insulin to assist the human body in utilizing blood glucose. It regulates metabolism by promoting the absorption of glucose into the blood. Objective: This work aimed to create an electrochemical biosensor based on magnetic graphene nanomaterial to measure insulin levels in athletes` blood. Method: A magnetic graphene nanocomposite created by graphene oxide (GO) and Fe-Ni bimetallic oxides on a glassy carbon electrode was synthesized using the electrochemical deposition method (GCE). Results: The immediate electrical deposition of Fe-Ni bimetallic oxide nanoparticles with the spherical shape on the GO nanosheet without aggregations was validated by structural characterizations of Fe-Ni/GO/GCE using XRD and SEM. The electrochemical results for insulin determination showed good sensitivity and anti-interference capability. The applicability and accuracy of the proposed electrochemical sensor to detect insulin were explored by blood serum samples from sportsmen. Conclusion: The results assigned acceptable RSD values (3.31% to 4.30%) and confirmed the feasibility of the proposed sensor for detecting athletes` blood insulin.